2005
DOI: 10.1152/jn.01137.2004
|View full text |Cite
|
Sign up to set email alerts
|

Nature of the Transition Between Two Modes of External Space Perception in Tilted Subjects

Abstract: A striking feature of visual verticality estimates in the dark is undercompensation for lateral body tilt. Earlier studies and models suggest that this so-called Aubert (A) effect increases gradually to around 130 degrees tilt and then decays smoothly on approaching the inverted position. By contrast, we recently found an abrupt transition toward errors of opposite sign (E effect) when body tilt exceeded 135 degrees . The present study was undertaken to clarify the nature of this transition. We tested the subj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
37
1

Year Published

2006
2006
2011
2011

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(48 citation statements)
references
References 20 publications
10
37
1
Order By: Relevance
“…Such a polarized stimulus has the advantage that it allows a more precise instruction of the task without influencing the accuracy of SVV adjustments (Kaptein and Van Gisbergen 2005). The arrow was projected onto the center of a sphere in front of the subject.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Such a polarized stimulus has the advantage that it allows a more precise instruction of the task without influencing the accuracy of SVV adjustments (Kaptein and Van Gisbergen 2005). The arrow was projected onto the center of a sphere in front of the subject.…”
Section: Methodsmentioning
confidence: 99%
“…The roll-dependent decay in precision of SVV estimates (De Vrijer et al 2008;Kaptein and Van Gisbergen 2005;LechnerSteinleitner 1978;Mittelstaedt 1983;Schoene and Udo de Haes 1968) has previously been associated mainly with the properties of the otolith organs (nonuniform distribution of otolith afferents in the roll plane, nonlinear firing rates), being optimally tuned along the whole-body upright position (Tarnutzer et al 2009b). Such an eminent role in verticality perception, however, can be assigned only to the otolith organs, provided there is clear experimental evidence for a modulation of SVV accuracy and precision in a head-fixed reference frame.…”
Section: Reference Frame Of the Graviceptive Sensory Systems And Of Tmentioning
confidence: 99%
“…Several earlier investigations showed that roll-tilted subjects may have a rather accurate estimate of body tilt but may yet show a large A-effect in their SVV settings (Kaptein and Van Gisbergen 2004;Mast and Jarchow 1996;Mittelstaedt 1983). Mittelstaedt (1983) attributes this apparent disparity to the tendency to use the body axis as a partial reference for verticality judgments in the context of the SVV task, but not in the perception of body tilt.…”
Section: Methodological Aspectsmentioning
confidence: 99%
“…However, many reports showed that stationary subjects, tilted sideways in darkness, make systematic errors when adjusting a luminous line parallel to the perceived direction of gravity. At large tilt angles, the subjective visual vertical (SVV) deviates toward the long-body axis [Aubert effect (A-effect)], as if tilt is underestimated, with errors amounting to 35°when the body is tilted 120° (Kaptein andVan Gisbergen 2004, 2005;Mittelstaedt 1983Mittelstaedt , 1989Schöne 1964;Udo de Haes 1970;Van Beuzekom and Van Gisbergen 2000). For small body tilts (Ͻ30°), these errors are generally much smaller and may even reverse sign [Müller effect (E-effect)].…”
mentioning
confidence: 99%
“…It is very unlikely that G vis 1 because the full range of orientations (0 -360°) has to be coded, which is possible only when G vis ϭ 1. Further indications come from line-orientation estimates (Kaptein and Van Gisbergen 2005;Van Beuzekom et al 2001). Based on these FIG. 5.…”
Section: What Determines Spatial Orientation Constancy?mentioning
confidence: 99%